Proactive Personality, Career Success, dan Career Adaptability pada Karyawan PT Kereta Api Indonesia Daop 8 Surabaya - Tri Siwi Agustina; Ivan Rizky Muhammad (Jurnal Bisnis dan Keuangan, 2019)
Proactive personality is an important factor in a boundaryless career. The reason is, in the boundaryless career period, the work environment becomes uncertain and the challenges in a career are increasingly complex. Therefore, there is a need for an adaptive attitude in running a career. Proactive personality is seen as a form of career adaptability. This study analyzes the rela- tionship between proactive personality, career adaptability and career success (subjective and ob- jective). Samples from this study are 41 people from employees of PT KAI DAOP 8 Surabaya which is included in the State-Owned Enterprises (BUMN). The respondents’ data were analyzed using Partial Least Square (PLS) using the SmartPLS 3.0 program. The results of this study indicate that when proactive personalities increase, career adaptability and subjective career success will in- crease too. While the other results of this study are when proactive personality increases, it does not significantly influence objective career success. Similarly, increasing career adaptability does not significantly influence objective career success.